Enhancement of in vitro anti-proliferative activity and intestinal membrane permeation of thai medicinal plant extracts selected from the MANOSROI II database by loading in chitosan-thioglycolic acid (TGA) nanoparticles - Boonpisuttinant K. (2017)
Chitosan (CTS) and chitosan-thioglycolic acid (CTS-TGA) nanoparticles loaded with four aqueous extracts of Thai anti-cancer medicinal plants were prepared by ionic interaction with tripolyphosphate (TPP). The averages sizes, zeta-potentials and PDI of the CTS and CTS-TGA nanoparticles loaded with the aqueous extracts were in range of 309.09±66.3 to 394.6±71.3 nm, +1.73±2.39 to +2.39±0.79 mV and 0.354±0.021 to 0.555± 0.012; and 225.0±38.7 to 311.5±51.4 nm, 1.46±0.63 to 3.59±0.45 and 0.229±0.069 to 0.398±0.087, respectively, whereas 244.8±48.1 nm, +3.56±0.71 mV and 0.350; and 174.2±23.2 nm, +3.22±0.85 mV and 0.207, respectively were observed in blank CTS and CTS-TGA nanoparticles, respectively. All extracts from the medicinal plants showed anti-proliferative activity on HeLa and HepG2 cancer cell lines. The CTS and CTS-TGA nanoparticles can significantly enhance anti-proliferative activity of the extracts on Hela and HepG2 cancer cells (p < 0.05). The extract of T. triandra loaded in CTS nanoparticles and the extract of A. marmelos loaded in CTS-TGA nanoparticles exhibited the highest decreased cell viability of 7.28 and 6.37 folds, respectively. The in vitro kinetic release and the intestinal membrane permeation of the medicinal plant extracts determined as quinazoline through the rat intestinal membrane by Ussing type chamber across the freshly excised rat intestinal mucosa were similar to quinazoline with the release of zero order plot, whereas the release of those loaded in the CTS and CTS-TGA nanoparticles were conformed with the Higuchi's equation. Thiolation significantly enhanced the permeation of the CTS nanoparticles with the highest transport enhancement ratio (R) of 1.45 (p < 0.05). The CTS-TGA nanoparticles significantly improved the permeation of quinazoline with the highest (R) of 1.62 (p < 0.05). This study has demonstrated the anti-proliferative activity on human cancer cell lines and permeation enhancements of the Thai anti-cancer medicinal plant extracts by loading in the CTS and CTS-TGA nanoparticles, which can be further developed to oral natural products. © 2012 American Scientific Publishers. All rights reserved.